The Spanish Archaeological and Archaeobiological Mission at Sharjah (SAAMS): Al Madam–al Khudairah Project; Life in the Oasis–Death on the Hills - Cerro Linares, Carmen del (Near Eastern archaeology, 2024)
The Universidad Autónoma de Madrid has been working since the mid-1990s at the Iron Age village of al Madam located in the interior of the Oman peninsula, in the Emirate of Sharjah (UAE). In 2019 we received permission to excavate a necropolis in the municipality of al Khudairah (Sharjah), opening a new potential for the study of the funerary world of ancient Magan, as this area was called in the Mesopotamian texts. With the permission of the local authorities, and so as to balance study of the village with that of the necropolis, our team expanded and added a permanent contingent of archaeobiologists to our roster. Thus in February 2020 began the Spanish Archaeological and Archaeobiological Mission at Sharjah (SAAMS) and a new project: the "Al Madam-al Khudairah Project: Life in the Oasis-Death on the Hills."